Urinary sodium excretion predicts blood pressure response to spironolactone in patients with resistant hypertension independent of aldosterone status. Issue 5 (May 2016) - Ghazi, Lama; Dudenbostel, Tanja; Lin, Chee Paul; Oparil, Suzanne; Calhoun, David A.
Abstract : Objective: Resistant hypertension (RHTN), blood pressure (BP) at least 140/90 mmHg despite using at least three different medications, including a diuretic, is associated with high dietary sodium and hyperaldosteronism. Mineralocorticoid receptor antagonists are recommended for treatment of RHTN, however, BP response to these agents varies widely. In the current analysis, we assessed predictors of BP response to spironolactone in patients with RHTN. Methods: We retrospectively evaluated the BP response to adding spironolactone 12.5–25 mg to existing medications. A favorable BP response was defined as a reduction in SBP of at least 10 mmHg. Tested variables included baseline characteristics and biochemical parameters. Results: A total of 79 patients with RHTN were included in the analysis. Evaluated patients were more likely women (53.2%) and African-American (55.8%); were generally obese (76%) and were prescribed an average of four antihypertensive medications. Baseline SBP was 153.6 ± 22.3 mmHg; addition of spironolactone resulted in a mean reduction of 15.5 ± 20.7 mmHg. Patients with high urinary sodium excretion (≥200 mEq/24 h) had a significantly greater BP reduction compared with patients with normal excretion (<200 mEq/24 h) ( P  = 0.008). Multivariable analysis identified 24 h urinary sodium excretion as a significant predictor of BP response ( P  = 0.021) after controlling for potential confounders, including primary aldosteronism. Conclusion: The antihypertensive effect of spironolactone is positively related to urinary sodium excretion regardless of aldosterone status. These findings suggest that mineralocorticoid receptor antagonists may be of preferential benefit in counteracting the BP effects of high dietary sodium.